2017
DOI: 10.1002/jat.3564
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subchronic immunotoxicity of four different types of aluminum‐based nanoparticles

Abstract: Nanoparticles (NPs) have recently emerged as an inhalable pollutant, owing to their applications, aluminum-based NPs (Al-NPs) have been prioritized for toxicity testing. In the current study, we compared the pulmonary biopersistence and subsequent toxicity of four different types of Al-NPs (two rod-type aluminum oxide NPs [AlONPs] with different aspect ratios [short (S)- and long (L)-AlONPs], spherical aluminum cerium oxide NPs [AlCeO , AlCeONPs] and spherical γ-aluminum oxide hydroxide nanoparticles [AlOOHNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Ultrafine particles have been identified in primary aluminum smelters and pot rooms (53). Concerning animal data, pulmonary inflammation and cytotoxicity (54), an increase in the number of immune cells in BAL fluid (55,56) and levels of IL-6, macrophage inflammatory protein-1α (MIP-1α), and monocyte chemoattractant protein-1α (GM-CSF) were reported after aluminum oxide ENM inhalation. Overall, the lack of epidemiological studies on possible adverse health effects prevents definite conclusions on the impact that aluminum oxide ENM may have on the health of exposed workers and possible markers indicative for early detection of biological alterations.…”
Section: Aluminum Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafine particles have been identified in primary aluminum smelters and pot rooms (53). Concerning animal data, pulmonary inflammation and cytotoxicity (54), an increase in the number of immune cells in BAL fluid (55,56) and levels of IL-6, macrophage inflammatory protein-1α (MIP-1α), and monocyte chemoattractant protein-1α (GM-CSF) were reported after aluminum oxide ENM inhalation. Overall, the lack of epidemiological studies on possible adverse health effects prevents definite conclusions on the impact that aluminum oxide ENM may have on the health of exposed workers and possible markers indicative for early detection of biological alterations.…”
Section: Aluminum Oxidementioning
confidence: 99%
“…Furthermore, explicit pathologies induced by ENM exposure have not yet been demonstrated in studies of exposed workers. The respiratory system has been reported as the primary target organ for the inflammogenic potential of both carbon-, and metal-or metal-oxide-based ENM in workplace and experimental settings, although some conflicting evidence in this regard may be due to the different physico-chemical characteristics of ENM, in terms of particle size (149), surface functionalization/coating (56,77,96,102), solubility (40), particle dispersion (114), residual impurities (121) as well as level and duration of exposures (129). This is important information considering that the respiratory tract is the primary route of entry of ENM in occupational settings.…”
Section: Summary Of Data and Occupational Health Considerationsmentioning
confidence: 99%
“…However, Al 2 O 3 NM seems to induce cytotoxicity in the lungs. In a previous study with mice it was shown that exposure to Al 2 O 3 increased LDH level from BALF 13 weeks after exposure, along with IL-6, MIP-1a and GM-CSF; but a high number of neutrophils was not observed [ 62 ]. In another study, Lu et al [ 63 ] tested 4 different Al 2 O 3 NMs in rats, and found that only 1 type of Al 2 O 3 induced inflammation 24 h after intratracheal instillation, with no changes in LDH activity in BALF.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and occupational studies have shown the hazard of inhalation exposure to Al, Cr and Ni to human health. Workplace exposure to airborne particles containing these elements has been associated with several respiratory disorders, such as pulmonary fibrosis, asthma, chronic obstructive lung disease, lung cancer and cardiovascular disease [27][28][29][30][31][32][33][34]. Several in vivo and in vitro studies have also addressed the toxicity of the nanoforms of these elements.…”
Section: Discussionmentioning
confidence: 99%